Orofacial antinociceptive activity and anchorage molecular mechanism in silico of geraniol - Tereza Karla Vieira Lopes da COSTA; Mariana Silva BARROS; Renan Marrinho BRAGA; Jéssika de Oliveira VIANA; Frederico Barbosa de SOUSA; Luciana SCOTTI; Marcus Tullius SCOTTI; André Ulisses Dantas BATISTA; Reinaldo Nóbrega de ALMEIDA; Ricardo Dias de CASTRO (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract We aimed to evaluate the orofacial antinociceptive effect of geraniol in mice and its molecular anchorage mechanism. Seven mice per group (probabilistic sample) were treated with geraniol (12.5, 25 and 50 mg/kg, i.p.), morphine (6 mg/kg, i.p.) and vehicle (saline + Tween 80 at 0.2%, i.p.) 30 minutes prior to the beginning of the experiment. Injecting glutamate (25 μM), capsaicin (2.5 μg) and formalin (2%) into the right upper lip (perinasal) of the mouse induced nociception. Behavioral analysis of the animals considered the friction time (in seconds) of the mentioned region using hind or front paws by a researcher blinded to the treatment groups. The statistical analysis was performed blindly, considering α = 5%. The results showed that in the glutamate and capsaicin tests, concentrations of 25 mg/kg and 50 mg/kg presented antinociceptive activity (p < 0.005, power> 80%). In the formalin test, geraniol was able to reduce nociception at a concentration of 50 mg/kg (p < 0.005, power> 80%). In the molecular anchorage study, high values of binding between the evaluated substance and receptors of glutamate were observed (metabotropic glutamate receptor, -87.8501 Kcal/mol; N-methyl-D-aspartate, -86.4451 Kcal/mol; α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid, -85.6755 Kcal/mol). Geraniol presented orofacial antinociceptive activity, probably by interacting with glutamate-related receptors.